Ceramic active powder based on coal gangue as well as preparation method and application of ceramic active powder
By crushing, grinding and heat treatment of coal gangue, controlling its chemical composition and mineral phase, the problem of high impurity content after coal gangue treatment is solved, high-performance preparation of glass fibers is achieved, and production costs and energy consumption are reduced.
Patent Information
- Application Number
- CN202411257731.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the impurity content after coal gangue treatment is high, which cannot meet the production requirements of glass fibers, and the energy consumption and cost increase during the heat treatment process, affecting the performance of the powder.
By crushing, grinding, and removing iron, and performing fluidized bed heat treatment at a heat treatment temperature of 850-950°C, SiO2+Al2O3≥65wt%, Al2O3≥25wt%, Fe2O3≤0.5wt% to obtain high Ceramic active powder of the lingshi phase reduces impurity content and calcination loss, and improves the whiteness and stability of the powder.
It realizes the high strength, heat resistance and clarity and transparency of glass fibers, reduces the production cost of glass fibers, improves the uniformity and stability of powders, and reduces chemical oxygen consumption. It is suitable for the preparation of high-end glass fibers.
Smart Images

Figure HDA0005034592460000011 
Figure HDA0005034592460000021
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic active powder based on coal gangue, a preparation method and application thereof, and relates to CO4B, and specifically to the fields of lime, ceramics and other materials. Background Art
[0002] The main components of glass fiber are SiO2, Al2O3, etc. Mineral raw materials such as kaolin, pyrophyllite, and quartz can provide SiO2 and Al2O3 in glass fiber, so kaolin is an important source of raw materials for glass fiber. However, the quality of kaolin used in the preparation of glass fiber is relatively high and needs to be imported. Coal gangue is a solid waste discharged during the coal-related and coal-washing process, which also contains rich SiO2 and Al2O3. Coal gangue has a wide range of sources and low costs, so coal gangue can replace kaolin as a raw material for preparing glass fiber, which can not only achieve efficient and high-value utilization of coal gangue solid waste, but also effectively solve the problem of the source and stability of glass fiber raw materials.
[0003] Chinese invention patent CN202210740339.X discloses a method for preparing gangue-based active powder and solidifying radionuclide Se. A part of the gangue is mixed with an alkaline material and alkali-fused roasted to obtain an alkali-fused material; another part of the gangue is calcined at high temperature using residual coal as a heat source to obtain a gangue calcined material; the alkali-fused material is mixed and ground with the gangue calcined material, as well as a magnesium-based additive and pyrite to obtain a gangue-based active powder material, forming a geopolymer solidified body in which the radionuclide Se in the Se-containing solid waste is solidified. The prepared powder cannot be used to prepare glass fiber. Chinese invention patent CN202310711759.X discloses a system and method for preparing active powder by activating coal gangue in a tunnel kiln. The system uses coal gangue as raw material and adds an activating admixture, which effectively reduces the thermal activation temperature of the coal gangue and stimulates the activity of the coal gangue. At the same time, mechanical activation is combined to further stimulate the activity of the coal gangue, thereby increasing the activation rate of the coal gangue and the utilization of the coal gangue. However, the mass content of Al2O3 in the powder is more than 10%, which is relatively low and is not suitable for the preparation of glass fiber. Summary of the invention
[0004] In order to reduce the content of impurities in coal gangue after treatment and make it suitable for the production and processing of glass fiber, the first aspect of the present invention provides a ceramic active powder based on coal gangue, the chemical composition of the ceramic active powder is SiO2+Al2O3≥95wt%, wherein the Al2O3 content is 30-45wt%, and the Fe2O3 content is ≤0.5wt%.
[0005] As a preferred embodiment, the main mineral phase of the ceramic active powder is a metakaolinite phase, and does not contain a mullite phase. The particle size of the ceramic active powder is ≤300 mesh, COD is ≤300, and the powder whiteness is ≥80%.
[0006] The second aspect of the present invention provides a method for preparing ceramic active powder based on coal gangue, comprising the following steps:
[0007] S1 crushes, grinds and removes iron from coal gangue;
[0008] S2 is then placed in a heat treatment system for heat treatment, and after cooling, ceramic active powder is obtained.
[0009] As a preferred embodiment, in the coal gangue, SiO2+Al2O3≥65wt%, wherein the Al2O3 content is ≥25wt%.
[0010] As a preferred embodiment, the Fe2O3 content in the coal gangue is ≤0.5wt%, and the ignition loss of the coal gangue is ≤30%. The main mineral phase of the coal gangue is kaolinite phase.
[0011] The inventor found in the experimental process that the powder obtained by treating coal gangue with SiO2+Al2O3≧65%, Al2O3≥25wt can be applied to the preparation of glass fiber, and the glass fiber has high strength, good heat resistance, and high clarity and transparency of the material. The possible reason is that the powder obtained by preparing glass fiber with high strength and good heat resistance by using SiO2 and Al2O3 containing appropriate weight parts. If it is lower than the preferred weight parts, the content of other impurities will increase, reducing the strength of the glass fiber. If the content of Al2O3 is too high, it will affect the clarification temperature of the glass liquid and increase the production cost of the glass fiber. And if the Fe2O3 impurity content in the coal gangue is too high, it will affect the stability of the clarified liquid of the glass fiber. The coal gangue ignition loss is too high. In the process of preparing the powder, in order to exclude carbon and mixed organic matter as much as possible and reduce COD (chemical oxygen demand), a longer heat treatment time and heat treatment temperature are required, which will increase the energy consumption of heat treatment and increase the cost of powder manufacturing. It is also possible to cause the formation of mullite phase in the mineral, affecting the performance of the powder.
[0012] As a preferred embodiment, the particle size of the coal gangue after crushing is less than 10 mm, and the particle size of the coal gangue after grinding is ≤ 200 mesh. Preferably, the particle size of the coal gangue after grinding is ≤ 300 mesh.
[0013] As a preferred embodiment, the grinding method is selected from a vertical mill or a roller mill.
[0014] As a preferred implementation manner, the Fe2O3 content of the coal gangue after iron removal is ≤0.3wt%.
[0015] As a preferred embodiment, after the coal gangue is ground, a dry electromagnetic iron removal process is used to remove part of the iron and iron compounds in the raw materials and the crushing process.
[0016] As a preferred embodiment, the heat treatment system includes a primary cyclone preheater, a secondary cyclone preheater, a fluidized bed heat treatment furnace, a high-temperature powder collector, and a fluidized bed cooler.
[0017] After iron removal, the material is first sent to the primary cyclone preheater 2 by the quantitative feeder 1 for preheating for 5-10 seconds to remove free water, and then enters the secondary preheater 3 for high-temperature preheating for 3-5 seconds to further remove bound water, structural water and some organic matter. After preheating and dehydration, the material is pneumatically conveyed to the fluidized bed heat treatment furnace 4 for further dehydration, decarbonization and impurity removal. The heat-treated powder passes through the high-temperature powder collector 6 and the fluidized bed cooler 7 for collection. The high-temperature powder collector discharges 70% of the high-temperature hot gas into the secondary cyclone preheater 3 and the fluidized bed heat treatment furnace 4 as high-temperature preheating air and secondary air respectively, and 30% of the high-temperature hot gas enters the dust collector 10 after heat exchange and is directly discharged through the smoke window 11. If the material stays in the fluidized bed heat treatment furnace for too short a time, it is easy to cause incomplete removal of carbon and organic matter, affecting the quality and stability of the powder. On the contrary, if the residence time is too long, on the one hand, it will increase the investment cost of the kiln, and on the other hand, it will also affect the efficiency and cost of coal gangue powder making.
[0018] As a preferred embodiment, the temperature of the first-stage cyclone preheater is 150-300°C, the temperature of the second-stage cyclone preheater is 350-600°C, the temperature of the high-temperature powder collector is 700-850°C, and the temperature of the fluidized bed cooler is 150-350°C.
[0019] As a preferred implementation, the treatment temperature of the fluidized bed heat treatment furnace is 800-1000° C., and the heat treatment time is 5-10 s.
[0020] As a preferred embodiment, the treatment temperature of the fluidized bed heat treatment furnace is 850-950°C.
[0021] The inventor further found that under the preferred content of coal gangue, the best heat treatment temperature is 850-950°C. The possible reason is that at the preferred temperature, impurities in the coal gangue can be quickly removed. If the preferred temperature is exceeded, the silicon-aluminum spinel synthesized at low temperature by coal gangue will gradually transform into mullite, especially around 1100°C, the amount of mullite generated may reach more than 10wt%, resulting in a decrease in the suspension degree of the glass liquid. At the same time, the formation of mullite minerals will also seriously affect the drawing performance of the glass liquid. If the heat treatment temperature is lower than 850°C, the organic matter and interlayer carbon mixed in the coal gangue cannot be quickly removed in a short time, which will cause the powder COD to be too large and the whiteness to be reduced, thereby affecting the clarity, uniformity and glass fiber quality of the glass liquid.
[0022] The third aspect of the present invention provides an application of ceramic active powder based on coal gangue in the preparation of glass fiber.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The ceramic active powder based on coal gangue described in the present invention has high silicon and aluminum contents, low mullite content, few impurities, high sintering activity, small ignition loss, low COD, good performance uniformity, and can replace pyrophyllite or imported kaolin and be used in the preparation of high-end glass fiber.
[0025] (2) The gangue-based ceramic active powder of the present invention uses gangue solid waste as raw material, adopts a heat treatment temperature of 850-950° C. and a heat treatment time of 5-10 s, has a wide source of raw materials, low energy consumption, and low production cost.
[0026] (3) The gangue-based ceramic active powder of the present invention uses gangue with high aluminum and silicon content, low iron oxide content and low ignition loss as raw material. After heat treatment, the performance is stable and the chemical oxygen demand is low, which is about 60% lower than the chemical oxygen demand of 500-2000 mg / kg of traditional washed kaolin.
[0027] (4) The gangue-based ceramic active powder of the present invention has low impurity content, high whiteness, low temperature during heat treatment, short treatment time, low energy consumption, and high efficiency of gangue powder making.
[0028] (5) The gangue-based ceramic active powder of the present invention is used in the preparation of glass fibers. The glass fibers are of high and stable quality and have low cost. Large-scale industrial production of high-end glass fibers can be achieved, and high-value resource utilization of high-aluminum gangue solid waste can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the heat treatment process flow chart of the heat treatment system.
[0030] In the figure: 1. Feeder; 2. First-stage cyclone preheater; 3. Second-stage cyclone preheater; 3. Fluidized bed heat treatment furnace; 4. High-temperature powder collector; 5. Fluidized bed cooler; 6. High-temperature powder collector; 7. Fluidized bed cooler; 8. Screw feeder; 9. Silo; 10. Dust collector; 11. Smoke window.
[0031] Figure 2 The following are XRD patterns of coal gangue powders at different heat treatment temperatures according to the implementation of Example 1.
[0032] a: 1200℃; b: 1100℃; c: 1000℃; d: 950℃; e: 900℃; f: 850℃; g: 750℃; h: 600℃; i: unheat-treated coal gangue. DETAILED DESCRIPTION
[0033] Example 1
[0034] A method for preparing ceramic active powder based on coal gangue comprises the following steps:
[0035] S1 crushes, grinds and removes iron from coal gangue;
[0036] S2 is then placed in a heat treatment system for heat treatment, and after cooling, ceramic active powder is obtained.
[0037] In the coal gangue, SiO2+Al2O3 accounts for 74.74wt%, of which the Al2O3 content is 33.68wt%, the Fe2O3 content is 0.34wt%, and the loss on ignition of the coal gangue is 23.4%, which is derived from the coal gangue of Huadian Coal Mine.
[0038] The particle size of the coal gangue after crushing is less than 10 mm, and the particle size of the coal gangue after roller grinding is ≤300 meshes.
[0039] After the coal gangue is ground, a dry electromagnetic iron removal process is used to remove iron and iron compounds in the raw material and crushing process. The Fe2O3 content of the coal gangue after iron removal is ≤0.3wt%.
[0040] The heat treatment system comprises a primary cyclone preheater 2 , a secondary cyclone preheater 3 , a fluidized bed heat treatment furnace 4 , a high-temperature powder collector 6 , and a fluidized bed cooler 7 .
[0041] After iron removal, the material is first sent by the quantitative feeder 1 to the primary cyclone preheater 2 for preheating for 5 seconds to remove free water, and then enters the secondary preheater 3 for high-temperature preheating for 5 seconds to further remove bound water, structural water and some organic matter. After preheating and dehydration, the material is pneumatically conveyed to the fluidized bed heat treatment furnace 4 for further dehydration, decarbonization and impurity removal. The burner 5 provides energy for the fluidized bed heat treatment furnace. The heat-treated powder passes through the high-temperature powder collector 6 and the fluidized bed cooler 7 for collection. The high-temperature powder collector 6 discharges 70% of the high-temperature hot gas into the secondary cyclone preheater 3 and the fluidized bed heat treatment furnace 4 as high-temperature preheating air and secondary air respectively, and 30% of the high-temperature hot gas enters the dust collector 10 after heat exchange and is directly discharged through the smoke window 11. The powder collected by the fluidized bed cooler 7 enters the silo 9 through the screw feeder 8 and is stored for standby use.
[0042] The temperature of the first-stage cyclone preheater is 250°C, the temperature of the second-stage cyclone preheater is 450°C, the temperature of the high-temperature powder collector is 800°C, and the temperature of the fluidized bed cooler is 250°C.
[0043] The treatment temperature of the fluidized bed heat treatment furnace is 950° C., and the heat treatment time is 6 seconds.
[0044] A ceramic active powder based on coal gangue, wherein the chemical composition is 96.98wt% of SiO2+Al2O3, wherein the Al2O3 content is 44.28wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, the whiteness is 82%, the COD is 85mg / kg, the high temperature ignition loss is small, and the powder can be used in the field of glass fiber.
[0045] Example 2
[0046] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as that of Example 1, except that the treatment temperature of the fluidized bed heat treatment furnace is 900° C. and the heat treatment time is 5 s.
[0047] A ceramic active powder based on coal gangue, wherein the chemical composition is 96.43wt% of SiO2+Al2O3, wherein the Al2O3 content is 43.86wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, the whiteness is 78%, the COD is 115mg / kg, the high temperature ignition loss is small, and the powder can be used in the field of glass fiber.
[0048] Example 3
[0049] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as that of Example 1, except that the treatment temperature of the fluidized bed heat treatment furnace is 850° C. and the heat treatment time is 8 s.
[0050] A ceramic active powder based on coal gangue, wherein the chemical composition is 95.78wt% of SiO2+Al2O3, wherein the Al2O3 content is 43.16wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, the whiteness is 70%, the COD is 328mg / kg, the high temperature ignition loss is small, and the powder can be used in the field of glass fiber.
[0051] Example 4
[0052] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as Example 1, except that in the coal gangue, SiO2+Al2O3 is 69.25wt%, of which the Al2O3 content is 27.01wt%, and the Fe2O3 content is 0.37wt%. The loss on ignition of the coal gangue is 29.2%, and it is derived from the coal gangue of Suancigou Coal Mine.
[0053] The treatment temperature of the fluidized bed heat treatment furnace is 900° C., and the heat treatment time is 8 seconds.
[0054] A ceramic active powder based on coal gangue, wherein the chemical composition is 97.32wt% of SiO2+Al2O3 by weight, wherein the Al2O3 content is 37.53wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, does not contain a mullite phase, has a whiteness of 71%, a COD of 168mg / kg, and a small high-temperature ignition loss, and the powder can be used in the field of glass fiber.
[0055] Example 5
[0056] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as Example 4, except that the treatment temperature of the fluidized bed heat treatment furnace is 850° C. and the heat treatment time is 10 s.
[0057] A ceramic active powder based on coal gangue, wherein the chemical composition is 96.28wt% of SiO2+Al2O3, wherein the Al2O3 content is 37.24wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, does not contain a mullite phase, has a whiteness of 64%, a COD of 420mg / kg, has a small high-temperature ignition loss, and has a high sintering activity. The powder can be used in the field of glass fiber.
[0058] Comparative Example 1
[0059] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as that of Example 1, except that the treatment temperature of the fluidized bed heat treatment furnace is 1100° C. and the heat treatment time is 5 s.
[0060] A ceramic active powder based on coal gangue, wherein the chemical composition is SiO2+Al2O3 of 97.21wt%, wherein the Al2O3 content is 44.64wt%, and the Fe2O3 content is ≤0.5wt%. The mineral phase of the ceramic active powder contains a small amount of cristobalite and 5wt% of mullite phase, the whiteness is 89%, and the COD is 50mg / kg.
[0061] Although the powder has high silicon and aluminum contents and low COD, the formation of mullite phase affects the drawing quality of glass liquid, so the powder is not suitable for use in the glass fiber field.
[0062] Comparative Example 2
[0063] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as Example 1, except that in the coal gangue, SiO2+Al2O3 is 55.5wt%, of which the Al2O3 content is 21.35wt%, and the Fe2O3 content is 0.17wt%. The loss on ignition of the coal gangue is 41.2%, and it comes from red-burning coal gangue.
[0064] The treatment temperature of the fluidized bed heat treatment furnace is 800° C., and the heat treatment time is 10 seconds.
[0065] A ceramic active powder based on coal gangue, wherein the chemical composition is SiO2+Al2O3 of 92.66wt%, wherein the Al2O3 content is 34.28wt%, and the Fe2O3 content is ≤0.5wt%. The main mineral phase of the ceramic active powder is a metakaolinite phase, the whiteness is 58%, and the COD is 780mg / kg.
[0066] The powder has low whiteness and high COD, which will affect the clarity of glass liquid when used as raw material. It is not suitable for application in the field of glass fiber.
[0067] Comparative Example 3
[0068] A method for preparing ceramic active powder based on coal gangue, the specific implementation method is the same as Example 1, except that in the coal gangue, SiO2+Al2O3 is 79.48wt%, of which the Al2O3 content is 19.78wt%, and the Fe2O3 content is 0.83wt%. The loss on ignition of the coal gangue is 14.2%, and it comes from coal gangue from coal mines in the United States and Japan.
[0069] The treatment temperature of the fluidized bed heat treatment furnace is 950° C., and the heat treatment time is 5 seconds.
[0070] A ceramic active powder based on coal gangue, wherein the chemical composition is 94.37wt% of SiO2+Al2O3, wherein the Al2O3 content is 22.86wt%, and the Fe2O3 content is 0.97wt%. The main mineral phases of the ceramic active powder are silicon aluminum spinel, quartz and other impurity phases, the whiteness is 34%, and the COD is 260mg / kg.
[0071] The powder has a relatively low aluminum content, low whiteness, and high iron content, and is not suitable for application in the glass fiber field.
Claims
1. A ceramic active powder based on coal gangue, characterized in that: The chemical composition of the ceramic active powder is SiO2+Al2O3≥95wt%, wherein the content of Al2O3 is 30-45wt%, and the content of Fe2O3 is ≤0.5wt%.
2. A method for preparing ceramic active powder based on coal gangue according to claim 1, characterized in that: The following steps are involved: S1 crushes, grinds and removes iron from coal gangue; S2 is then placed in a heat treatment system for heat treatment, and after cooling, ceramic active powder is obtained.
3. The method for preparing ceramic active powder based on coal gangue according to claim 2, characterized in that: In the coal gangue, SiO2+Al2O3≥65wt%, wherein the content of Al2O3 is≥25wt%.
4. The method for preparing ceramic active powder based on coal gangue according to claim 2, characterized in that: The Fe2O3 content in the coal gangue is ≤0.5wt%, and the ignition loss of the coal gangue is ≤30%.
5. The method for preparing ceramic active powder based on coal gangue according to claim 2, characterized in that: The particle size of the coal gangue after crushing is less than 10mm, and the particle size of the coal gangue after grinding is ≤200 meshes.
6. The method for preparing ceramic active powder based on coal gangue according to claim 2, characterized in that: The Fe2O3 content of the coal gangue after iron removal is ≤0.3wt%.
7. The method for preparing ceramic active powder based on coal gangue according to claim 2, characterized in that: The heat treatment system comprises a primary cyclone preheater, a secondary cyclone preheater, a fluidized bed heat treatment furnace, a high-temperature powder collector, and a fluidized bed cooler.
8. The method for preparing ceramic active powder based on coal gangue according to claim 7, characterized in that: The temperature of the first-stage cyclone preheater is 150-300°C, the temperature of the second-stage cyclone preheater is 350-600°C, the temperature of the high-temperature powder collector is 700-850°C, and the temperature of the fluidized bed cooler is 150-350°C.
9. The method for preparing ceramic active powder based on coal gangue according to claim 7, characterized in that: The treatment temperature of the fluidized bed heat treatment furnace is 800-1000° C., and the heat treatment time is 5-10s.
10. An application of the ceramic active powder based on coal gangue according to claim 1, characterized in that: Used in the preparation of glass fiber.
Citation Information
Patent Citations
Active ceramic powder and preparation process thereof
CN115448697A
Low-energy-consumption coal gangue resource utilization production system and production method
CN115536037A
